Experimental analysis of mechanical properties of selected takraw balls in Malaysia - Adam, Nor Mariah (Penerbit Universiti Malaysia Pahang, 2014)
Sepak Takraw is a popular sport among the Southeast Asian countries and various brands of takraw balls are available in the local market to suit the needs of players. In this study, four different takraw balls commonly used by the Malaysian takraw players were selected for testing of mechanical properties by using compression and fatigue analysis. It was found that the GE takraw balls were more suitable to be used by Malaysian takraw players due to higher fatigue life and tensile strength. This finding is particularly useful for the local sport academy in deciding which ball is to be used in the future takraw competitions.